The Portrayal of Love Languages in Kristy Boyce’s Novel Hot British Boyfriend (2021): A Study of Young Adult Literature Using Gary Chapman’s Theory - Muhammad Danial; Dewi Nurmala; Ratna Sari Dewi (Surakarta English and Literature Journal, 2025)
This study aims to examine the portrayal of love languages in Kristy Boyce’s novel Hot British Boyfriend (2021) by applying Gary Chapman’s Five Love Languages framework, which consists of words of affirmation, acts of service, receiving gifts, quality time, and physical touch. The research employs a qualitative descriptive method, focusing on narrative excerpts, dialogues, and character actions that reflect the expressions of love between the protagonist, Ellie, and two male characters, Will and Dev. The findings reveal that Dev demonstrates stronger consistency in using supportive and meaningful love expressions, particularly through quality time and acts of service, which highlight his emotional investment and stability in the relationship. In contrast, Will is portrayed as more focused on physical touch and surface-level affirmations, suggesting a less emotionally grounded approach to love. These results show that the use of Chapman’s theory provides valuable insights into how adolescent romance is represented in young adult literature. Furthermore, the study highlights how different love language preferences can reveal character depth, relational quality, and the dynamics of emotional intimacy in literary works.